Geochemistry of a Triassic dyke swarm in the North Patagonian Massif, Argentina. Implications for a postorogenic event of the Permian Gondwanide orogeny - González, Santiago Nicolás (2016)
Fil: González, Santiago Nicolás. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - Patagonia Norte; Argentina.